Randomised controlled trial of Antiglucocorticoid augmentation (metyrapone) of antiDepressants in Depression (ADD Study) - I Nicol Ferrier (Efficacy and Mechanism Evaluation, 2015)
Background: Depressed patients who do not respond to second-line antidepressant drugs are characterised as suffering from treatment-refractory depression (TRD). Chronic psychosocial stress hypothalamic–pituitary–adrenal (HPA) axis dysfunction is associated with attenuated responses to antidepressants. Corticosteroid co-administration reduces the increase in forebrain 5-hydroxytryptamine with selective serotonin reuptake inhibitors, whereas antiglucocorticoids have the opposite effect. A Cochrane review suggesting that antiglucocorticoid augmentation of antidepressants may be effective in treating TRD included a pilot study of the cortisol synthesis inhibitor, metyrapone. The Antiglucocorticoid augmentation of antiDepressants in Depression (ADD Study) was a multicentre randomised placebo-controlled trial of metyrapone augmentation of serotonergic antidepressants in patients with TRD. Objective: To determine the efficacy and safety of augmentation of standard serotonergic antidepressants with metyrapone 500 mg twice a day for 3 weeks in patients with TRD. Methods: A total of 165 patients with moderate to severe TRD aged 18–65 years were randomised to metyrapone 500 mg twice daily or placebo for 3 weeks, in addition to ongoing serotonergic antidepressants. The primary outcome was improvement in Montgomery–Åsberg Depression Rating Scale (MADRS) score 5 weeks after randomisation estimated using analysis of covariance. Secondary outcomes included the degree of persistence of treatment effect for up to 6 months, and also safety and tolerability of metyrapone. ADD included substudies investigating the potential mechanism of action of metyrapone, and utilised a comparator group of healthy participants. Results: The estimated mean difference for each of our study outcomes between randomised groups, 5 weeks post randomisation (allowing for variation between centres and whether or not patients originate from primary or secondary care) was MADRS –0.51 [95% confidence interval (CI) –3.48 to 2.46]; Beck Depression Inventory (BDI) –2.65 (95% CI –6.41 to 1.10); Clinical Anxiety Scale 0.46 (95% CI –1.20 to 2.12); State–Trait Anxiety Inventory 1.2 (95% CI –0.6 to 3.0); European Quality of Life-5 Dimensions 0.015 (95% CI –0.069 to 0.099); EuroQol visual analogue scale 5.6 (95% CI –0.7 to 12.0); and Young Mania Rating Scale –0.04 (95% CI –0.52 to 0.45). The differences were not statistically significant and were small in relation to the change from baseline in both groups that was observed immediately after completion of therapy. Endocrinological data required for compliance assessment are not yet available. HPA function, similar in patients and control subjects, was not associated with differing clinical responses. Neuropsychological impairments were found, along with changes in brain structure and function, but no effect of metyrapone was seen on these measures. Discussion: The inclusion criteria led to the sample being broadly representative of patients with TRD, within the UK NHS, with high anxiety and BDI scores. Metyrapone augmentation of antidepressants is not efficacious for outpatients with TRD who are moderately depressed. There was no obvious benefit associated with the use of metyrapone, either on the primary outcome or over the period of follow-up, and this negative result extended to other secondary outcomes. Metyrapone was well tolerated. There were no serious adverse events attributable to it and adverse events were as common with the placebo. HPA axis function was not associated with differing clinical or neuropsychological outcomes. Conclusions: The results of the study suggest that although metyrapone augmentation was well tolerated, it is ineffective in the treatment of refractory depression. This finding is contrary to a previous proof of principle study in more acutely unwell patients. Future research should consider whether or not antiglucocorticoid treatments, such as metyrapone, should be targeted at patients with confirmed hypercortisolaemia. Trial registration: Current Controlled Trials ISRCTN45338259. Funding details: This study was funded by the National Institute for Health Research Efficacy and Mechanism Evaluation (EME) programme, a MRC and NIHR partnership.